Kekuatan Eksitensi Bisnis Waralaba Sebagai Perjanjian Innominaat Di Indonesia - Ferdinand Nicholas; Urbanisasi - (Law, Development and Justice Review, 2023)
The Indonesian state system is a prosperous country where a safe, comfortable and peaceful society is the benchmark. Welfare development is supported by economic development in the business sector, one of which is the franchise business. Franchise is a business venture that provides benefits for the parties involved in the agreement. Franchise agreements are regulated in general in the Civil Code, Government Regulations and Minister of Commerce Regulations governing franchising. Franchise agreements are like agreements in general that are regulated in the Civil Code and are bound by the principles of the agreement. However, in reality there is often an imbalance or deviation from the principles committed by one of the parties. Therefore it is needed, a law that specifically regulates the existence of a franchise agreement. Legislation is made by the House of Representatives which must be drafted and ratified as soon as possible so as to create legal certainty and protection for the parties.